Quality of Extemporaneous Preparation Containing Theophylline, Salbutamol Sulphate and Methylprednisolone - Sri Hartati Yuliani; Bernadetta Karina Sekar Maheswari; Melynia Sintha Dewi; Michael Raharja Gani; Dina Christin Ayuning Putri (Sanata Dharma University, 2023)
Capsule preparations containing theophylline, salbutamol sulfate, and methylprednisolone were frequently prescribed in a private hospital in Yogyakarta. Theophylline is a narrow therapeutic index drug. Extemporaneous preparation products that contain narrow therapeutic index drugs have to meet the quality requirement. This study aimed to evaluate the quality of the capsule preparations. The sample was taken from a private hospital in Yogyakarta. The samples were assessed for physical characteristics, content uniformity, and chemical stability during storage. The result found that the physical characteristics of the product were good. The coefficients of variance of the content uniformity percentage for theophylline, salbutamol sulfate, and methylprednisolone were 11.96%, 3.33%, and 45.74%, respectively. During 30 days of storage, the content of theophylline, salbutamol sulfate, and methylprednisolone decreased by 1.44%, 7.64%, and 15.7%, respectively. Capsule preparations containing theophylline, salbutamol sulfate, and methylprednisolone did not meet the quality requirement.